The Influence of Scientific Vocabulary on the Speaking Ability of Students at the Al-Amien Prenduan Sumenep Institute of Islamic Studies - Maharani; Luthfatul Qibtiyah (Penerbit Hellow Pustaka, 2025)
Giving scientific vocabulary is very important when going to communicate with people. speaking is a process of conveying information, ideas or ideas from the speaker to the listener. vocabulary is one of the various elements of language that is very important because of its function as the formation of expressions, sentences, and discourse. the purpose of this study was to determine whether or not the influence of the provision of scientific vocabulary on the ability to speak as well as, how much influence the provision of scientific vocabulary on the ability to speak, in this study using quantitative research methods of causal type, this study was conducted at Al-Amien Prenduan Islamic Boarding School, Institut Dirosat Islamiyah Al-Amien Prenduan, and obeservation as supporting questionnaire while the subjects of this study were taken from 25 respondents. the data analysis technique used is the critical price table r and calculated using spss 25 with a simple linear regression formula. based on the results showed that the value of F count on the variable ability to speak is 0.331<0.05 and t count is greater than the table (2.191>2.100). R square value of the variable ability to speak by 33.1% while the remaining 67.9% influenced by other variables outside the research based on these values, , means the provision of scientific vocabulary significant effect on the ability to speak mahasantri semester III Institute Dirosat Islamiyah Al-Amien Prenduan.